Learning curve of laparoscopic hysterectomy in a zonal hospital setting: a retrospective analysis of 102 cases operated by a single surgeon - Kumar, Praveen; Kapur, Krishan; Bhat, P. Mohan; Karkhanis, Nikhil (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The aim of this study was to analyse the learning curve and clinical efficacy of the art of laparoscopic hysterectomy in a zonal hospital setting. Methods: We conducted a retrospective analysis of 102 women who underwent laparoscopic hysterectomy (LAVH/ TLH) by a single surgeon after post-graduation for benign uterine pathology in a zonal hospital setting. They were divided into two groups of first 50 cases (Group I) and next 52 cases (Group II). The primary outcome was the learning curve of the operating gynaecologist in terms of reduction in duration of surgery, reduced perioperative complications, increasing percentage of TLHs with time. Results: 102 women underwent laparoscopic hysterectomy for the benign uterine pathology successfully. Surgical outcomes of laparoscopic hysterectomy in terms of mean operative time was 135 mins (Group I) vs 93 mins (Group II), estimated blood loss 255 ml (Group I) vs 140 ml (Group II), hospital stay 05 days (Group I) vs 03 days (Group II), duration of postoperative analgesia 07 days (Group I) vs 05 days (Group II). As the surgical experience increased, patients with bigger uterine size (>10-week size) were taken up for hysterectomy, percentage of TLH increased in Group II as compared to Group I (42.31% vs 18%), with decreasing complications and shorter recovery time. Conclusions: Laparoscopic hysterectomy (LAVH/ TLH) has a short learning curve and it's a feasible and beneficial surgical modality for treating benign uterine pathology even in a zonal hospital setting (low resource setting).